Incidence and severity of hypoglycaemia in type 2 diabetes by treatment regimen: A UK multisite 12‐month prospective observational study. Issue 7 (4th April 2019) - Dunkley, Alison J.; Fitzpatrick, Claire; Gray, Laura J.; Waheed, Ghazala; Heller, Simon R.; Frier, Brian M.; Davies, Melanie J.; Khunti, Kamlesh; ,
Abstract : Aims: To determine the incidence and severity of self‐reported hypoglycaemia in a primary care population with type 2 diabetes. The study also aimed to compare incidence by treatment regimen. Materials and methods: A prospective observational study in 17 centres throughout the UK was conducted. Recruitment was based on treatment regimen (metformin alone, sulphonylurea‐, insulin‐ or incretin‐based therapy). Participants were asked to keep a blood glucose diary and self‐report hypoglycaemia episodes [non‐severe (self‐treated) and severe (requiring external help)] over a 12‐month period. Results: Three hundred and twenty‐five participants were enrolled, of whom 274 (84%) returned ≥1 monthly diaries. Overall, 39% reported experiencing hypoglycaemia; 32% recorded ≥1 symptomatic, 36% ≥1 non‐severe, and 7% ≥1 severe episodes. By treatment, incidence (events per person/year) for any hypoglycaemia type was 4.39 for insulin, 2.34 for sulphonylurea, 0.76 for metformin, and 0.56 for incretin‐based therapy. Compared with metformin, risk of non‐severe hypoglycaemia was 3 times higher for participants on sulphonylureas and > 5 times higher for those on insulin [incidence rate ratio (IRR) 3.02 (1.76‐5.18), P < 0.001, and IRR 5.96 (3.48‐10.2), P < 0.001, respectively]. For severe episodes, the incidence for sulphonylurea (0.09) was similar to metformin (0.07) and incretin‐based therapy (0.07); for insulin the risk remained almost 5 times higher than metformin [incidence 0.32; IRR 4.55 (1.28‐16.20), P = 0.019]. Conclusions: Hypoglycaemia represents a substantial burden for people with type 2 diabetes. Sulphonylureas and insulin are both associated with a risk of reported non‐severe hypoglycaemia, but only insulin with severe episodes. This suggests the importance of the continued use of sulphonylureas in appropriate patients with type 2 diabetes.